Democratic capitalism at the crossroads technological change and the future of politics - Boix, Carles (Princeton University Press, 2019)
An incisive history of the changing relationship between democracy and capitalismThe twentieth century witnessed the triumph of democratic capitalism in the industrialized West, with widespread popular support for both free markets and representative elections. Today, that political consensus appears to be breaking down, disrupted by polarization and income inequality, widespread dissatisfaction with democratic institutions, and insurgent populism. Tracing the history of democratic capitalism over the past two centuries, Carles Boix explains how we got here--and where we could be headed.Boix looks at three defining stages of capitalism, each originating in a distinct time and place with its unique political challenges, structure of production and employment, and relationship with democracy. He begins in nineteenth-century Manchester, where factory owners employed unskilled laborers at low wages, generating rampant inequality and a restrictive electoral franchise. He then moves to Detroit in the early 1900s, where the invention of the modern assembly line shifted labor demand to skilled blue-collar workers. Boix shows how growing wages, declining inequality, and an expanding middle class enabled democratic capitalism to flourish. Today, however, the information revolution that began in Silicon Valley in the 1970s is benefitting the highly educated at the expense of the traditional working class, jobs are going offshore, and inequality has risen sharply, making many wonder whether democracy and capitalism are still compatible.Essential reading for these uncertain times, Democratic Capitalism at the Crossroads proposes sensible policy solutions that can help harness the unruly forces of capitalism to preserve democracy and meet the challenges that lie ahead.